The Use of Audio-Visual Methods to Improve Language Development of Children with Speech Delay Aged 5–6 Years: A Classroom Action Research in Early Childhood Education - Rusita Yuli (Journal of Teaching and Education, 2025)
This study aims to improve the language development of children with speech delay aged 5–6 years through the implementation of audio-visual learning methods in early childhood education. Language development is a fundamental aspect of early childhood growth and serves as a foundation for cognitive, social-emotional, and academic development. However, some children experience speech delay, which may hinder their ability to communicate effectively. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were two children aged 5–6 years identified as experiencing speech delay at PAUD Mentari Bengalon. Data were collected through observation checklists based on developmental indicators and analyzed descriptively using percentage improvements across cycles. The findings indicated a consistent increase in children’s language development from the pre-cycle stage to Cycle I and Cycle II. The use of audio-visual media, such as instructional videos and picture cards, was found to enhance children’s vocabulary acquisition, pronunciation, attention, and motivation to participate in learning activities. The study concludes that audio-visual methods are effective in supporting language development in children with speech delay and recommends their integration into inclusive early childhood learning practices.